Internalization of Religious Tolerance Through Cross-Cultural Dialogue in Kendal’s Art Performances - Agus Riyadi; Nur Hamid; Saerozi Saerozi (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2022)
The intolerance symptoms in several regions of Indonesia are increasingly worrying as transnational actions proliferate. However, in some remote villages of Java island, cultural and Islamic spiritual capitals are still found, manifested through various local pearls of wisdom in performing arts, as seen in the Cacaban community, Singorojo, and Kendal Regency. Skills can be used as media for cross-cultural dialogues between Islam and Java to build harmony. This study examines the debate between Islamic values and Javanese cultures to find an accommodative model of acculturation between Islam and Javanese wisdom in cultivating the values of tolerance in moderate religious life. This study implements a qualitative-ethnographic-interpretive approach based on the phenomenological hermeneutic paradigm. It shows that the patterns of cross-cultural dialogue in Cacaban Kendal society are carried out through Jaran Kepang, Karawitan, and Wayang Orang performances. Meanwhile, the reproduction of cultural acculturation is found explicitly in the praxis of life in the form of world views; beliefs or ideology; social attitudes; rites or ceremonies; social principles, norms, and regulations; habits, and behavior in social interactions. The internalization of the tolerance system can be categorized into three main principles, namely: (1) the principle of religious freedom, (2) the principle of respect for the existence of other religions, and (3) the principle of freedom in doing good things and being fair to everyone.